The Lighthouse Chapel International – Its Growth from 1988 And 2013 - Emmanuel Nterful (Noyam Publishers, 2019)
The Lighthouse Chapel International, a charismatic denomination that started almost three decades ago in a coastal suburb of Accra, Korle Gonno has witnessed glowing achievements. It has grown from its humble beginnings by the grace of God from a five member congregation to a worldbeater. It is domiciled in seventy-two countries, all continents of the world, trained over three thousand pastors and built over five hundred and fifty church buildings. This article seeks to bring to the fore, what has accounted for the church’s massive growth, its strategies, growth and missions, important milestones among other things.